PEMANFAATAN LIMBAH TANAMAN JAGUNG SOLUSI KETERSEDIAAN PAKAN ALTERNATIF BAGI TERNAK SAPI DI DESA URAUR KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Tatipikalawan, Jomima Martha; Patty, Christian W.; Ririmasse, Pieter Melianus; Sangadji, Insun (Universitas Pattimura, 2024)
Silage has proven to be an effective way to extend the availability of forage throughout the year. Silage technology transfer brings great benefits in maximizing the use of existing feed sources, improving livestock nutrition, and reducing the impact of limited feed on livestock productivity. The purpose of this activity is to transfer corn straw silage technology which is expected to overcome feed shortages under certain conditions, improve feed quality and maintain the continuity of cattle feed availability in Uraur village. This activity was carried out in Uraur Village, Kairatu District, with partners of cattle breeder groups and the Participation Institute for the Development and Empowerment of the Maluku Protestant Church (PARPEM-GPM) Uraur. The method of activity used is action review which includes concrete actions to overcome problems, collaboration with partners and action authentication. The result of this activity is an increase in the knowledge and skills of farmers and farmers motivated to introduce corn straw silage technology and the desire to use it as an alternative feed for solutions to improve the quality and continiutas of feed which can further increase the growth and production of cattle optimally.